2020
DOI: 10.7717/peerj.10246
|View full text |Cite
|
Sign up to set email alerts
|

Non-SARS-CoV-2 genome sequences identified in clinical samples from COVID-19 infected patients: Evidence for co-infections

Abstract: Background In December 2019, an ongoing outbreak of pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2/ 2019-nCoV) infection was initially reported in Wuhan, Hubei Province, China. Early in 2020, the World Health Organization (WHO) announced a new name for the 2019-nCoV-caused disease: coronavirus disease 2019 (COVID-19) and declared COVID-19 to be a Public Health Emergency of International Concern (PHEIC). Cellular co-infection is a critical determinant of viral fitness and infect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Coinfections, compared with single infections, may lead to changes in transmission of the pathogen, progression of clinical symptoms, and the adverse effects associated with any given infection, which ultimately determines the management of infectious diseases 182‐185 . The inability of conventional methods to detect coinfection, in the absence of sufficient evidence, in turn, can result in underdiagnosis of coinfections 186 . Coinfections or mixed infections have been reported to negatively affect the efficiency of diagnostic methods used for detection of SARS‐CoV‐2; for instance, RT‐PCR may not be the optimal diagnostic test for diagnosis of COVID‐19 in patients with influenza A virus coinfection 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coinfections, compared with single infections, may lead to changes in transmission of the pathogen, progression of clinical symptoms, and the adverse effects associated with any given infection, which ultimately determines the management of infectious diseases 182‐185 . The inability of conventional methods to detect coinfection, in the absence of sufficient evidence, in turn, can result in underdiagnosis of coinfections 186 . Coinfections or mixed infections have been reported to negatively affect the efficiency of diagnostic methods used for detection of SARS‐CoV‐2; for instance, RT‐PCR may not be the optimal diagnostic test for diagnosis of COVID‐19 in patients with influenza A virus coinfection 18 .…”
Section: Discussionmentioning
confidence: 99%
“…[182][183][184][185] The inability of conventional methods to detect coinfection, in the absence of sufficient evidence, in turn, can result in underdiagnosis of coinfections. 186 Coinfections or mixed infections have been reported to negatively affect the efficiency of diagnostic methods used for detection of SARS-CoV-2; for instance, RT-PCR may not be the optimal diagnostic test for diagnosis of COVID-19 in patients with influenza A virus coinfection. 18 In contrast, nucleic acid amplification test would be a suitable method for detection of influenza virus RNA in the case of coinfection with SARS-CoV-2.…”
Section: Diagnosis Of Viral Coinfectionsmentioning
confidence: 99%
“…As previously described, Kraken2 generated accurate taxonomic identification for bacteria with very fast speed [37,38]. However, only a few studies have used Kraken2 for fungal and viral microbiome studies [39,40]. In this study, we have shown that Kraken2 is a powerful tool for identifying bacteria, fungi, and viruses.…”
Section: Discussionmentioning
confidence: 55%
“…COVID-19-associated AIHA has been previously described [ 1 , 2 ], Furthermore, this patient had evidence of recent parvovirus B19-mediated pure red cell aplasia, which significantly worsened his anemia in the setting of ongoing hemolysis. Co-infection with SARS-CoV-2 and parvovirus B19 has been found to cause severe cardiac, neurologic, and hematologic manifestations [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%